2015
DOI: 10.1103/physreve.92.030302
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of mass at the periphery ofN-isopropylacrylamide-co-acrylic-acid microgels at high temperatures

Abstract: We investigate poly(N-isopropylacrylamide) (pNIPAM) microgels randomly copolymerized with large mol % of protonated acrylic acid (AAc), finding that above the lower critical solution temperature the presence of the acid strongly disrupts pNIPAM's collapse, leading to unexpected new behavior at high temperatures. Specifically, we see a dramatic increase in the ratio between the radius of gyration and the hydrodynamic radius above the theoretical value for homogeneous spheres, and a corresponding increase of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…For crosslinked pNIPAM microgels synthesized without AAc or another comonomer, R g /R h typically increases with T , approaching the homogeneous sphere value at high T [4]. Previous experiments performed on the same crosslinked microgels used in this study found R g /R h to increase above 3/5 at high T and low pH, where the AAc groups are not ionized [6]. Thus, since the only difference in the pH 5 suspensions of crosslinked microgels in this study is the presence of partially ionized AAc, the decreasing and unusually low R g /R h must be a direct consequence of charge.…”
Section: Crosslinked Microgelssupporting
confidence: 53%
See 1 more Smart Citation
“…For crosslinked pNIPAM microgels synthesized without AAc or another comonomer, R g /R h typically increases with T , approaching the homogeneous sphere value at high T [4]. Previous experiments performed on the same crosslinked microgels used in this study found R g /R h to increase above 3/5 at high T and low pH, where the AAc groups are not ionized [6]. Thus, since the only difference in the pH 5 suspensions of crosslinked microgels in this study is the presence of partially ionized AAc, the decreasing and unusually low R g /R h must be a direct consequence of charge.…”
Section: Crosslinked Microgelssupporting
confidence: 53%
“…Using microgels composed of NIPAM copolymerized with acrylic acid (AAc) and crosslinked with poly(ethylene glycol) diacrylate (pEG-d), we recently showed that at pH 3, where the AAc is uncharged, this copolymer can frustrate the collapse of pNIPAM at high temperatures, leading to heterogeneous clumping of polymer within the particle and concentration of mass at the periphery [6]. In this work, we observe a segregation of mass at the particle center of the same particles due to a completely different mechanism when the AAc groups are partially charged.…”
Section: Introductionmentioning
confidence: 99%
“…During the microgel synthesis, the degrees of freedom for the polymer strands are intentionally reduced by forming covalent cross-links between polymer chains. The chemical cross-linking itself is a nonequilibrium process, and it does not necessarily progress uniformly, which may lead to spatial fluctuations, gradients, and heterogeneities in the microgel particle architecture 20 . For a complete understanding of a microgel colloid as a material building block or a carrier, it is imperative to know the spatial distribution of polymer and cross-link densities on the nanoscale.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, these are not synonymous with the model‐inferred mesh sizes (Figure 3D) which are on the order of nanometers, consistent with the expectations of a gel [ 41,42 ] including P(AAc‐co‐NIPAm) networks. [ 43 ] As such, what is observed in Figure 4 is the hierarchical mesh of the gels, indicating that (at least in the dry state) chains cluster together. Note that for both gels, heterogeneity may be exacerbated by the fact that the scans depicted in Figure 4 were taken from the cross‐sectional area of the fracture plane, where significant damage must have occurred.…”
Section: Mechanical Effects Of Compositionmentioning
confidence: 82%